2014
DOI: 10.1111/jfq.12082
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Quality and Antioxidant Enzyme Activities of Bunched and Topped Radish (Raphanus sativusL.) Plants during Storage at 5 or 10C

Abstract: Quality changes of bunched and topped radishes (Raphanus sativus L.) during postharvest storage were investigated. Bunched radish plants, topped roots and detached leaves were stored at 5 or 10C for 9 days. Yellowing and wilting of leaves during storage at 10C were the main visual quality deteriorations in bunched radishes. Leaf detachment reduced respiration and ethylene production rates and weight loss of roots, and resulted in lower ascorbic acid, antioxidant capacity and phenolic content especially during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 29 publications
(35 reference statements)
5
17
1
Order By: Relevance
“…To simulate such open storage practices, we stored radishes in plastic crates only with or without curing which depicted higher water loss resulting in shriveling (Figure 2(e)) and deterioration of visual quality from the beginning of storage. Tsouvaltzis and Brecht [20] observed about 1.3% weight loss of topped radish root after 9 days of storage at either 5 ∘ C or 10 ∘ C which supported our weight loss result of unpacked roots as we found nearly 5% loss of fresh weight after 30 days of storage. However, Ayub et al [6] found severe weight loss of radishes (about 52%) just after 3 days of storage when radishes were stored at room temperature (20 ± 2 ∘ C) without leaves.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…To simulate such open storage practices, we stored radishes in plastic crates only with or without curing which depicted higher water loss resulting in shriveling (Figure 2(e)) and deterioration of visual quality from the beginning of storage. Tsouvaltzis and Brecht [20] observed about 1.3% weight loss of topped radish root after 9 days of storage at either 5 ∘ C or 10 ∘ C which supported our weight loss result of unpacked roots as we found nearly 5% loss of fresh weight after 30 days of storage. However, Ayub et al [6] found severe weight loss of radishes (about 52%) just after 3 days of storage when radishes were stored at room temperature (20 ± 2 ∘ C) without leaves.…”
Section: Resultssupporting
confidence: 88%
“…This treatment also showed nearly similar values of * and WI until 60 days of storage and therefore received the highest visual quality scores (later discussion) among the treatments. del Aguila et al [19] reported that the * values of whole radish roots (without packaging) remained unchanged during a 10-day storage period regardless of storage temperature up to 10 ∘ C. This implies that color changes of whole radish root are more insensitive to that of leaf or leafy vegetables and well documented by Tsouvaltzis and Brecht [20]. Therefore, many food industries which use radish root as one of the food ingredients store radish carelessly at lower temperature, especially in Korea.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…The value for radish root is comparable with values reported in a previous work for the same product of 240 mg GAE/100 g d.m. (Tsouvaltzis & Brecht, 2014) but higher compared to the value of 122 mg GAE/100 g d.m. reported by Pushkala et al (2013).…”
Section: Colormentioning
confidence: 61%
“…Moreover, they play a significant role as antioxidants in the protective effect of plantderived foods (Balasundram, Sundram, & Samman, 2006). In particular, Radish (Raphanus sativus L.) is a root vegetable of Cruciferaceae family and it is an important vegetable crop worldwide (Tsouvaltzis & Brecht, 2014). Radish composition was found to be of highly medicinal and nutritional value.…”
Section: Introductionmentioning
confidence: 99%